The Association Between Parenting Style, Severity Symptoms of ADHD, and Parental Competence among Mothers of Children with ADHD - Kong-in, Pattaraporn; Prasartpornsirichoke, Jirada; Preechawuttidech, Sasithorn (Journal of the Psychiatric Association of Thailand, 2023)
Objective: Raising a child with attention deficit hyperactivity disorder (ADHD) is challenging. Mothers of children with this disorder are obliged to face doubts about their competence. The severity of ADHD and parenting styles can have an impact on maternal perception of competence, which has detrimental effects on childcare. The objective of the study was to investigate the association between the type of parenting style, the severity of ADHD, and parenting competence among Thai mothers of children with ADHD. Methods: This was a cross-sectional descriptive study. We recruited 84 mothers of children with ADHD who visited the Outpatient Child and Adolescent Psychiatry Clinic at King Chulalongkorn Memorial Hospital from 1 January to 30 June 2022 for the study. Participants were asked to complete questionnaires as follows: Demographic data questionnaire, short form of the Parenting Styles and Dimensions Questionnaire (PSDQ), Swanson, Nolan and Pelham IV scale (SNAP-IV), The Parenting Sense of Competence in Thai version. Data on diagnoses and comorbidities of ADHD were extracted from their medical records. Frequency, mean, and standard deviation were used to present descriptive statistics of the participants. The independent T test and Pearson correlation were used to investigate the relationship between parenting style, severity of ADHD, and mother’s perception of competence. In the study, a significance level of 0.05 was applied. Result: The average scores of authoritarian parenting style (r = -0.376, p<0.001) and permissive parenting style (r = -0.530, p<0.001), and the sum scores of SNAP-IV in the domains of inattention (r = -0.583, p<0.001), hyperactive-impulsive (r = -0.483, p<0.001), and ODD (r = -0.561, p <0.001) were significantly negatively correlated with maternal perception of parenting competence. Conclusion: The finding was in with previous studies that found authoritarian and permissive parenting styles, and that worse attention deficits were substantially associated with mothers’ perceptions of their own inadequate parenting practices. Therefore, the promotion of adaptive parenting techniques and the reduction of ADHD symptoms may aid mothers in feeling more competent, which would enhance their quality of life.